Measurement of carbonaceous aerosol with different sampling configurations and frequencies - Y. Cheng; K.-B. He (Atmospheric Measurement Techniques, 2015)
A common approach for measuring the mass of organic carbon (OC) and elemental carbon (EC) in airborne particulate matter involves collection on a quartz fiber filter and subsequent thermal–optical analysis. Although having been widely used in aerosol studies and in PM2.5 (fine particulate matter) chemical speciation monitoring networks in particular, this measurement approach is prone to several types of artifacts, such as the positive sampling artifact caused by the adsorption of gaseous organic compounds onto the quartz filter, the negative sampling artifact due to the evaporation of OC from the collected particles and the analytical artifact in the thermal–optical determination of OC and EC (which is strongly associated with the transformation of OC into char OC and typically results in an underestimation of EC). The presence of these artifacts introduces substantial uncertainties to observational data on OC and EC and consequently limits our ability to evaluate OC and EC estimations in air quality models. In this study, the influence of sampling frequency on the measurement of OC and EC was investigated based on PM2.5 samples collected in Beijing, China. Our results suggest that the negative sampling artifact of a bare quartz filter could be remarkably enhanced due to the uptake of water vapor by the filter medium. We also demonstrate that increasing sampling duration does not necessarily reduce the impact of positive sampling artifact, although it will enhance the analytical artifact. Due to the effect of the analytical artifact, EC concentrations of 48 h averaged samples were about 15 % lower than results from 24 h averaged ones. In addition, it was found that with the increase of sampling duration, EC results exhibited a stronger dependence on the charring correction method and, meanwhile, optical attenuation (ATN) of EC (retrieved from the carbon analyzer) was more significantly biased by the shadowing effect. Results from this study will be useful for the design of China's PM2.5 chemical speciation monitoring network, which can be expected to be inaugurated in the near future.